Prevalence of Carbapenemases in Carbapenem-Resistant Acinetobacter baumannii Isolates from the Kingdom of Bahrain - Nouf Al-Rashed; Khalid M. Bindayna; Mohammad Shahid; Nermin Kamal Saeed; Abdullah Darwish; Ronni Mol Joji; Ali Al-Mahmeed (MDPI AG, 2023)
Background: Acinetobacter baumannii is regarded as a significant cause of death in hospitals. The WHO recently added carbapenem-resistant Acinetobacter baumannii (CRAB) to its global pathogen priority list. There is a dearth of information on CRAB from our region. Methods: Fifty CRAB isolates were collected from four main hospitals in Bahrain for this study. Bacterial identification and antibiotic susceptibility tests were carried out using the BD PhoenixTM and VITEK-2 compact, respectively. Using conventional PCR, these isolates were further screened for carbapenem resistance markers (blaOXA-51, blaOXA-23, blaOXA-24, blaOXA-40, blaIMP, blaNDM, blaVIM, and blaKPC). Results: All of the isolates were resistant to imipenem (100%), meropenem (98%), and cephalosporins (96-98%), followed by other commonly used antibiotics. All these isolates were least resistant to gentamicin (64%). The detection of resistance determinants showed that the majority harbored blaOXA-51 (100%) and blaIMP (94%), followed by blaOXA-23 (82%), blaOXA-24 (46%), blaOXA-40 (14%), blaNDM (6%), blaVIM (2%), and blaKPC (2%). Conclusion: The study isolates showed a high level of antibiotic resistance. Class D carbapenemases were more prevalent in our CRAB isolate collection. The resistance genes were found in various combinations. This study emphasizes the importance of strengthening surveillance and stringent infection control measures in clinical settings to prevent the emergence and further spread of such isolates.